Calcium and TFAM crosstalk in the mitochondrial life cycle in cardiomyocytes - Cardetti, Caitlyn (2023)
Calcium (Ca2+) links the electrical signals of the heart to the mechanical action of contraction in a process referred to as the cardiac excitation-contraction (EC) coupling, a process that consumes a large amount of adenosine triphosphate (ATP). The majority of ATP is produced in the mitochondria via oxidative phosphorylation (OXPHOS), which is linked to Ca2+ flux. The OXPHOS system is regulated by both the nuclear and mitochondrial genome, with mitochondrial transcription factor A (TFAM) being a major regulator of the latter. This mini review focuses on summarizing the limited literature implicating crosstalk between Ca2+ and TFAM in the adult cardiomyocyte throughout the mitochondrial life cycle: mitochondrial dynamics, biogenesis, and mitophagy. The goal of this review is to highlight gaps and fuel further investigation of the proposed Ca2+-TFAM axis. This research area has high potential to propel the development of therapeutic strategies targeting cardiovascular diseases such as heart failure.